2021
DOI: 10.1186/s42269-021-00546-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drought tolerance in Triticum aestivum L. seedlings using Azospirillum brasilense NO40 and Stenotrophomonas maltophilia B11

Abstract: Background The effectiveness of two PGPB; Azospirillum brasilense NO40 and Stenotrophomonas maltophilia B11 was investigated in enhancing the drought tolerance of wheat (Triticum aestivum L.) seedlings cultivar Gemiza9. The inoculated or uninoculated grains were sown in unsterilized sandy soil and watered normally untill the 8th day. Drought stress was initiated by completely withholding water for 7 days (until wilting). Samples were collected after 15 days from sowing to evaluate some growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…The root development and early flowering in sunflowers may be linked to the phytohormone synthesis and detection of phytohormone genes in the bacterial genome. The effect of the co-inoculation of endophytic bacteria genera, such as Stenotrophomonas, Bradyrhizobium, Pseudomonas, Kosakonia, and Azospirillum, on the growth parameters and yield of sunflowers and other crops under greenhouse experiments have been performed with success (Egamberdieva et al 2016;Youseif 2018;Singh et al 2020;Adeleke et al 2021;Kasim et al 2021). Furthermore, the sunflower yield enhancement by S. maltophilia JVB5 upon inoculation in the greenhouse corroborates the results of Adeleke et al (2021) who reported a significant difference in the yield of sunflowers inoculated with endophytic S. indicatrix BOVIS40.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The root development and early flowering in sunflowers may be linked to the phytohormone synthesis and detection of phytohormone genes in the bacterial genome. The effect of the co-inoculation of endophytic bacteria genera, such as Stenotrophomonas, Bradyrhizobium, Pseudomonas, Kosakonia, and Azospirillum, on the growth parameters and yield of sunflowers and other crops under greenhouse experiments have been performed with success (Egamberdieva et al 2016;Youseif 2018;Singh et al 2020;Adeleke et al 2021;Kasim et al 2021). Furthermore, the sunflower yield enhancement by S. maltophilia JVB5 upon inoculation in the greenhouse corroborates the results of Adeleke et al (2021) who reported a significant difference in the yield of sunflowers inoculated with endophytic S. indicatrix BOVIS40.…”
Section: Discussionsupporting
confidence: 76%
“…The ability of bacterial endophytes to fix phosphorus in the soil has played an important role in plant nutrition (Passari et al 2016). Endophytic S. maltophilia strains, namely, SEN 1 (Etesami & Alikhani 2016), B11 (Kasim et al 2021), SY-2 (Liaquat et al 2020), have been identified as phosphate solubilisers with the potential of enhancing plant growth. The phosphorus-solubilising potential of S. maltophilia JVB5 in a tricalcium medium was confirmed in the genome analysis, as diverse genes involving phosphate transport and metabolism were predicted in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…These osmolytes act synergistically with osmolytes synthesized by plants (such as glycine-betaine, soluble sugars, trehalose, and proline), act as osmoprotectants, and prevent cell damage caused by drought [ 93 ]. Thus, the accumulation of these osmolytes in plants, triggered by these microbes, influences an increase in tolerance to water stress [ 59 , 61 , 62 , 66 , 67 ].…”
Section: Stress Tolerance Mechanisms Mediated By Plant Growth-promoti...mentioning
confidence: 99%
“…Considering those strains selected from more arid environments, despite the fact that Paenibacillus amylolyticus B2A is not often referred to in the literature, here, we can see how this strain may be a good treatment to promote growth and improve tolerance to drought in plants. In the case of Stenotrophomonas maltophilia M1B, there are many reports of its capacity to induce higher shoots and longer roots, even under salt conditions; however, here, we show one of the few reports that this strain induces drought tolerance [ 117 ], and the first evaluation of their effect as root architecture enhancers, especially under drought conditions. Finally, plants treated with the strains Paenibacillus xylanexedens M1C and Enterobacter hormaechei B2C showed an interesting root thickness pattern, with thinner roots during continuous irrigation, and thicker roots than with any other treatment during drought.…”
Section: Discussionmentioning
confidence: 60%